Parenting Style Influences on Mothers and Daughters' Relationship on Astonishing Color of After - Joey Lidya; Liliek Soelistyo (Institute of Research and Community Outreach - Petra Christian University, 2022)
Young Adult fiction's popularity is at its peak right now due to the topic being related to the problems that teenagers are facing in today's era. One of those novels is Astonishing Color of After, a novel about the mother and daughter’s relationship between two generations, Dory with her mother, and Dory with her daughter, Leigh. This novel intrigues me to analyze the characteristics of Dory's and Dory's mother's parenting style, the influence of their parenting styles, and how it affects the mother's and daughter's relationship and their daughter's behavior problems. To analyze these three points, I will apply the authoritarian parenting style and permissive parenting style based on the types of parenting theory by Diana Baumrind. My analysis will show how Dory's and Dory's mother's parenting style is influenced by the culture and childhood trauma, and how their parenting styles affect the relationship between them and their daughter as well as their daughters' behavioral problems. This thesis will end with a conclusion that there is a line between when the parents become authority figures and when the parents become the companion of their children.